Biological hydrogen synthesis as an alternative energy of the future without environmental pollution? - Horst J. Koch (Romanian Journal of Ecology & Environmental Chemistry)
Direct photobiological hydrogen production would be an ideal solution for the environment, especially since it releases oxygen as a by-product with low environmental impact. The efficiencies achieved so far are not yet sufficient to compete economically - yield/expenditure - with the established processes of H2 production or even fossil fuels. Aspects of the safety, storage and transport of hydrogen must also be taken into account. In the field of photobiological hydrogen production, further scientific efforts are needed to understand molecular biology and increase the effectiveness of biophotolysis. In addition to genetic modifications, biophysical-biochemical methods such as the optimization of the environment (pH, temperature, gas and ion activities, etc.) or electric and magnetic fields are also discussed in order to optimize the yield of photosynthetic hydrogen. Ultimately, only innovative ideas – which will also contribute to the understanding of photosynthesis – in the field of the photosynthetic hydrogenase system can help this environmentally friendly and desirable approach to hydrogen production to achieve lasting economic success.